Ultrastructure of spermatozoa and spermatogenesis in Octopus minor (Sasaki, 1920) (Cephalopoda: Octopoda). Issue 31 (25th August 2016) - Qian, Yao-Sen; Zheng, Xiao-Dong; Wang, Wei-Jun; Yang, Jian-Min; Li, Qi
ABSTRACT: Octopus minor is widely distributed along the coastal areas of the west Pacific Ocean. This paper investigates spermatozoa, spermiogenesis from the testes, and spermatophores using light and electron microscopy. Mature spermatozoa are about 650 µm long. The head includes mainly the acrosome and nucleus. The acrosome consists of a striated cone surrounded by a single helix. The nucleus is cylindrical, homogeneous and of high electron density. The neck is short and connected with the head through the internal nuclear fossa. The axoneme connects the head, neck and tail. The tail is divided into middle, principal and final pieces. The '9 + 9 + 2' structure is surrounded by a mitochondrial sheath, which includes 9–11 mitochondria in transverse section. The sperm morphology is compared with the ultrastructure of other cephalopod spermatozoa, and taxonomic and phylogenetic implications are discussed.